2017
DOI: 10.5380/ce.v22i3.51355
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Associados À Satisfação Do Acompanhante Com O Cuidado Prestado À Parturiente

Abstract: RESUMO: O objetivo foi avaliar a satisfação do acompanhante com o cuidado prestado à mulher durante o trabalho de parto e nascimento e estimar fatores associados. Estudo transversal, realizado em Hospital Universitário no Sul do Brasil, foram entrevistados 369 acompanhantes de março a setembro 2015. As associações foram investigadas em análises bivariadas, razão de chance bruta e ajustada, através da regressão logística. A chance de satisfação foi maior nos acompanhantes que não presenciaram violência à mulher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
(43 reference statements)
1
8
0
9
Order By: Relevance
“…Regarding the right to accompany the pregnant woman, although the Law of the Companion has existed for more than a decade, most of the interviewees reported not having received guidance on the subject, as observed in other studies (12,14,(16)(17) . This may be related to a prenatal care directed to the clinical, not emphasizing the tenth step for prenatal quality care -to guide the woman on her rights guaranteed by law.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Regarding the right to accompany the pregnant woman, although the Law of the Companion has existed for more than a decade, most of the interviewees reported not having received guidance on the subject, as observed in other studies (12,14,(16)(17) . This may be related to a prenatal care directed to the clinical, not emphasizing the tenth step for prenatal quality care -to guide the woman on her rights guaranteed by law.…”
Section: Resultsmentioning
confidence: 83%
“…easy-to-understand instrument and the use of an accessible language are emphasized, to minimize limitations of understanding. In a previous study (14) , it was shown that there was no association between age, education, bond with the woman and previous experiences as a companion and satisfaction with the care provided to the woman.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…23 However, there is no unanimity in the findings of the literature on the fact, because the presence of the companion was not always able to totally inhibit the attitudes of the professionals that characterize verbal, physical and psychological violence. 24 Therefore, in order to achieve good results with the presence of the companion, it is necessary that it be effectively welcomed and recognized as an active subject, who needs to be oriented, prepared and encouraged to participate in the PDP. 3 The presence of the companion is not always welcomed, and the professionals with more time of service seem to be the most resistant to this practice, because they consider that it disrupts the team, leaving the insertion of this dependent related with the medical authorization.…”
Section: /16mentioning
confidence: 99%
“…8 The experience of being inserted in a care context marked by practices that go against the MS advocated in relation to obstetric care can lead them to moral suffering, characterized by painful psychological imbalance resulting from the impediment brought about by the environment so that the same their conduct in accordance with the ethical conduct they deem appropriate. 9 There are studies In the literature that address the moral suffering of nurses in different contexts, [10][11][12][13][14] as well as issues related to the childbirth humanization, 2,6,8,[15][16][17][18][19][20][21][22][23][24] but there are no national and international surveys that articulate the two aspects. Based on the foregoing, it is justified to carry out this study, which aimed to know the situations found in the work of nurses working in maternity and obstetric centers that can lead to moral suffering.…”
Section: Introductionmentioning
confidence: 99%